2014
DOI: 10.1038/cdd.2014.202
|View full text |Cite
|
Sign up to set email alerts
|

PARP-2 sustains erythropoiesis in mice by limiting replicative stress in erythroid progenitors

Abstract: Erythropoiesis is a tightly regulated process in which multipotential hematopoietic stem cells produce mature red blood cells. Here we show that deletion of poly(ADP-ribose) polymerase-2 (PARP-2) in mice leads to chronic anemia at steady state, despite increased erythropoietin plasma levels, a phenomenon not observed in mice lacking PARP-1. Loss of PARP-2 causes shortened lifespan of erythrocytes and impaired differentiation of erythroid progenitors. In erythroblasts, PARP-2 deficiency triggers replicative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 68 publications
3
89
0
1
Order By: Relevance
“…Moreover, recent reports have shown good efficacy of ATR or CHK1 inhibitors in hematopoietic tumors, mostly in in vitro settings (611). The particular efficacy of RSR inhibitors in lymphoid tumors is consistent with a preferential role for the RSR in the untransformed lymphoid compartment, exemplified by the frequent presence of anemia in mice suffering from RS (13, 2427). Overall, these analyses identify distinctively high levels of CHEK1 expression in lymphomas and leukemias, which could be indicative of underlying DNA replication stress.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, recent reports have shown good efficacy of ATR or CHK1 inhibitors in hematopoietic tumors, mostly in in vitro settings (611). The particular efficacy of RSR inhibitors in lymphoid tumors is consistent with a preferential role for the RSR in the untransformed lymphoid compartment, exemplified by the frequent presence of anemia in mice suffering from RS (13, 2427). Overall, these analyses identify distinctively high levels of CHEK1 expression in lymphomas and leukemias, which could be indicative of underlying DNA replication stress.…”
Section: Resultsmentioning
confidence: 53%
“…Second, inhibitors of ATR or its target CHK1 are toxic for several lymphomas and leukemias, including p53-deficient tumors (69, 11, 23). Moreover, the particular efficacy of RSR inhibitors in lymphoid tumors is consistent with a preferential role for the RSR in the untransformed lymphoid compartment, exemplified by the frequent presence of anemia in mice suffering from DNA replication stress (13, 2427). Finally, inhibition of ATR or inhibition of the related DNA damage response (DDR) kinase ATM predisposed primary stem cells infected with retroviruses expressing MLL-AF9, a fusion between the KMT2A and the transcription activator AF9, towards differentiation in vitro (28).…”
Section: Introductionmentioning
confidence: 57%
“…These studies revealed that PARP inhibition impacts on the differentiation of bone-marrow-derived cells (monocyte/macrophage, erythroid, or neutrophil and B cell lineages), neurons, spermatocytes, skeletal muscle, osteoblasts, and adipocytes (Virá g and Szabó , 2002). Later studies not only verified these results, but also extended them by implicating other PARP enzymes (e.g., PARP-2) in differentiation (Farré s et al, 2014;Szá ntó et al, 2012). The PARP-regulated molecular pathways in the regulation of differentiation are not fully elucidated; nonetheless, changes in chromatin structure, gene expression, mitochondrial activity, metabolism, and cell death are involved.…”
Section: Reviewmentioning
confidence: 85%
“…6). This leads to an accumulation of DNA damage in S-phase cells, S-phase stalling, and G2 delay (Sugimura et al 2008;Bryant et al 2009;Ray Chaudhuri et al 2012;Berti et al 2013;Dale Rein et al 2015;Farrés et al 2015;Maya-Mendoza et al 2018;Michelena et al 2018;Ronson et al 2018). In PARP1-depleted or inhibited cells, DSBs arise due to deprotection of stalled replication forks and their degradation by the MRE11 nuclease, due to impaired fork reversal, or from unligated Okazaki fragments encountered by replication forks (Lonn and Lonn 1985;Ray Chaudhuri et al 2012;Ying et al 2012;Hanzlikova et al 2018).…”
Section: Amplifying Genomic Instability With Parp and Parg Inhibitorsmentioning
confidence: 99%